Mediation : principles and regulation in comparative perspective - Hopt, Klaus J., 1940-; Steffek, Felix (Oxford : Oxford University Press, 2013)
'Mediation provides an attractive alternative to resolving disputes through court proceedings. Mediation promises just results in the interest of all parties concerned, a reduction of the court caseload, and cost savings for the parties involved as well as for the treasury. The European Directive on Mediation has given mediation in Europe new momentum by establishing a common framework for cross-border mediation. Beyond Europe, many states have tried in recent years to answer the question whether, and if so, how mediation should be regulated at a national and international level. The aim of this book is to promote the understanding and discussion of regulatory issues by presenting comparative research on mediation. It describes and analyses the law and practice of mediation in twenty-two countries. Europe is represented by chapters on mediation in Austria, Bulgaria, England, France, Germany, Greece, Hungary, Ireland, Italy, the Netherlands, Norway, Poland, Portugal and Spain. The world beyond Europe receives is analysed in chapters on mediation in Australia, Canada, China, Japan, New Zealand, Russia, Switzerland and the USA. Against this background, further chapters on fundamental issues identify possible regulatory models and discuss central principles of mediation law and practice. In particular, the work considers harmonisation and diversity in the law of mediation as well as the economic and constitutional problems associated with privatising civil justice. To the extent available, empirical research is used as a point of reference in the critical analysis.'--Publisher's website.
Mediation : comparison of laws, regulatory models, fundamental issues / Klaus J. Hopt and Felix Steffek -- Harmonisation and diversity in the private international law of mediation : the rhythms of regulatory reform / Nadja Alexander -- Privatising civil justice and the day in court / Rainer Kulms -- Mediation in Austria : the European pioneer in mediation law and practice / Markus Roth and David Gherdane -- Mediation in Bulgaria : legal regime, EU harmonisation and practical experience / Evgeni Georgiev and Christa Jessel-Holst -- Mediation in England and Wales : regulation and practice / Jens M. Scherpe and Bevan Marten -- Mediation in France : legal framework and practical experiences / Katrin Deckert -- Mediation in Germany : the German Mediation Act : alternative dispute resolution at the crossroads / Peter Tochtermann -- Mediation in Greece : a contemporary procedural approach in resolving disputes / Nikolaos K. Klamaris and Calliope G. Chronopoulou -- Mediation in Hungary : legal foundations, recent reforms, EU convergence / Christa Jessel-Holst -- Mediation in Ireland : growing importance of ADR driven by budgetary restraints and docket congestion : a cheap and easy way out? / Reinhard Ellger -- Mediation in Italy : alternative dispute resolution for all / Giuseppe De Palo and Lauren Keller -- Mediation in the Netherlands : between state promotion and private regulation / Liane Schmiedel -- Mediation in Poland : time for a quiet revolution? / Rafa Morek and ukasz Rozdeiczer -- Mediation in Portugal : growing up in a sheltered home / Jan Peter Schmidt -- Mediation in Spain : dealing with its first national regulation / Maria Luisa Villamarin Lopez -- Mediation in Australia : development and problems / Ulrich Magnus -- Mediation in Canada : one goal : different approaches to mediation in a state with federal and provincial jurisdictions / Reinhard Ellger -- Mediation in China : threat to the rule of law? / Knut B. Pissler -- Mediation in Japan : development, forms, regulation and practice of out-of-court dispute resolution / Harald Baum -- Mediation in New Zealand : widely accepted and successful / Heyo Berg -- Mediation in Norway :'faster, cheaper and more friendly' / Anneken Kari Sperr -- Mediation in Russia : regulation and practice / Dmitry Davydenko -- Mediation in Switzerland : a new approach in a conciliation-oriented tradition / Christoph Kumpan and Cathrin Bauer-Bulst -- Mediation in the USA : alternative dispute resolution between legalism and self-determination / Rainer Kulms.
Includes bibliographical references and index.
Keywords: Mediation -- European Union countries; Dispute resolution (Law) -- European Union countries; Mediation; Dispute resolution (Law)